Studying the resonance production cross-section of the heavy vectors within Heavy Vector Triplet model - Obikhod, T.V.; Petrenko, I.A. (Problems of Atomic Science and Technology, 2023)
In the context of TeV-scale extensions of the Standard Model both the experimental data and the construction of phenomenological models for the new heavy bosons searches are used by us. Heavy particles are predicted by the Simplified Model to describe only the on-shell resonance, have to be compared with LHC data. Bosons V’ created and decay according to the process pp‐>V’‐>Vh (V=W, Z) have certain properties that can be modeled within the Heavy Vector Triplet model using the Madgraph computer program. We have calculated the production cross sections of heavy particles using the experimental constraints in the parameter space (cₕ, cf) imposed on the benchmark scenario. The nature of the functional dependence of the cross section on the mass of the new boson, as well as the mechanism for the heavy particle production is studied with variation of the model parameters.